Spectrum of AI futures imaginaries by AI practitioners in Finland and Singapore: The unimagined speed of AI progress - Hautala, Johanna; Heino, Hanna (Elsevier, 2025)
AI teases our imagination: People have created various dystopian and utopian imaginaries of the era of AI. Although the key group creating and realizing AI-related futures imaginaries are the technology practitioners who research, develop, and apply AI, empirical research has focused on collective rather than individually interpreted imaginaries. Empirical research on individual practitioners’ futures imaginaries is necessary, as well as fine-tuning the related vocabulary to support individual and non-linear perspectives. We present an empirical study in which we interviewed 35 AI and robotics practitioners based in Finland and Singapore. We asked (1) what kind of best and worst futures imaginaries the practitioners of AI and robots envision and (2) how the practitioners imagine likely futures will emerge. As a result, we present three continuums. Along these continuums, the practitioners consider variations of likely futures: (1) the best, (2) in between, and (3) the worst. Our analysis reveals decisive questions behind the continuums regarding the agent in control, relations in practitioner communities and society, and justified concentration of power.